A Potential Epigenetic Marker Mediating Serum Folate and Vitamin B12 Levels Contributes to the Risk of Ischemic Stroke - Loo, Keat Wei; Heidi, Sutherland; Au, Anthony; Camilleri, Emily; Haupt, Larisa M.; Siew, Hua Gan; Griffiths, Lyn R. (Hindawi Publishing Corporation, 2015)
Stroke is a multifactorial disease that may be associated with aberrant DNA methylation profiles. We investigated epigenetic dysregulation for themethylenetetrahydrofolate reductase (MTHFR) gene among ischemic stroke patients. Cases and controls were recruited after obtaining signed written informed consents following a screening process against the inclusion/exclusion criteria. Serum vitamin profiles (folate, vitamin B12, and homocysteine) were determined using immunoassays. Methylation profiles for CpGs A and B in the MTHFR gene were determined using a bisulfite-pyrosequencingmethod.Methylation of MTHFR significantly increased the susceptibility risk for ischemic stroke. In particular, CpG A outperformed CpG B in mediating serum folate and vitamin B12 levels to increase ischemic stroke susceptibility risks by 4.73-fold. However, both CpGs A and B were not associated with serum homocysteine levels or ischemic stroke severity. CpG A is a potential epigenetic marker in mediating serum folate and vitamin B12 to contribute to ischemic stroke.